FDM of morphing composites using filaments with microfibers - Ng, Norman Wee Junn (Nanyang Technological University, 2020)
Fused deposition manufacturing (FDM) is a form of additive manufacturing that is becoming an increasing trend in manufacturing due to its versatility and its ability to manufacture components of complex geometries. The process uses a continuous filament that is extruded through a heated printer head with its movements controlled by a computer program in order to produce the specified geometry. Machines that can perform FDM are readily available in the market today in the form of 3D printers and vary vastly in their capabilities. A common material for the filament used in 3D printing is Polylactic Acid (PLA) known for its shape memory properties. In the extrusion process in FDM, it causes the polymer chains to be stretched, causing pre-stress to be generated along the print directions. It is found that upon activation via exposure to temperatures above its glass transition temperature (Tg), these chains would uncoil itself to relieve those pre-stress. Through this research, different print orientations and geometries are experimented to study the morphing properties of 3D printed PLA samples. Furthermore, the development of multi-stable composites that can exhibit fast transitions between multiple stable states can be attributed to the buildup of opposing pre-stresses between layers. By comparing the differences between Finite Element Analysis (FEA) simulations and the experimental samples, we can identify the stable equilibrium states as well as the constraints of conventional 3D printing in replicating these stable shapes. Through this research, it is found that it is possible for multi-stable behaviors to be driven by having multiple pre-stress fields in the same layer rather than a stress difference between layers. Even though filaments without microfibers are used, the contribution of the pre-stress fields and the FDM process to the morphing properties of a sample must first be verified before venturing into using filaments with microfibers. Therefore, it is key that we investigate the above-mentioned factors by using a conventional 3D printer to created samples with different geometries and configurations.